G436 An exploration of the significance of speech and language delay in congential hypothyroidism. (27th April 2016) - Saravanamuthu, A; Prentice, P; Peters, C
Abstract : Congenital hypothyroidism (CHT) is the most common congenital endocrine condition. Since newborn screening, early thyroxine therapy has significantly improved outcome, particularly in intellectual ability and growth. There is, however, continued evidence of subtle cognitive impairment. Aim: To ascertain the prevalence of speech and language delay in CHT and if more targeted speech and language therapy (SALT) would be beneficial. Method: From September–December 2014 thirty questionnaires were completed in CHT follow-up clinics for children aged 1.9–4.0 years. Retrospective information on speech and language milestones and areas of particular parental concern, were collected. Confounding factors considered included multilingualism, siblings, nursery attendance and family history. Results: 53% had evidence of speech and language delay, classified as not achieving a milestone by a 'red flag' age or having less words than the minimum expected. Parental concerns affected 37% of the cohort. Despite this only 10% received SALT input. 43% of study households were multilingual, so it was difficult to remove as a confounding factor. However, there were similar rates of delay in this group (54%) and those with English as a first language (53%). Numbers without siblings, not in nursery, or with a family history of delay, were too small to assess their impact on language development. Conclusion: The data suggests there is a high degree of speech and language delay and concern in this population, with so few referred to SALT. We recommend further investigation prospectively with a larger study group and 6–12 monthly follow-up. Other factors relevant to outcome such as aetiology, initial biochemistry, starting thyroxine dose and time to normalisation of thyroid function must also be recorded. Ideally children would have formal developmental testing covering all domains. In lieu of this, those deemed high risk by a questionnaire could be assessed by SALT in more depth to decide if further input is required. We proffer that assessment of, and support for, speech and language development should be a routine aspect of CHT follow-up.